Предмет:
МатематикаАвтор:
аноним5 1/4 * (12 - t) - 3 3/4 * (-t - 24) = (5 * 4 + 1)/4 * (12 - t) - (3 * 4 + 3)/4 * (-t - 24) = (20 + 1)/4 * (12 - t) - (12 + 3)/4 * (-t - 24) = 21/4 * (12 - t) - 15/4 * (-t - 24) = 21/4 * 12 - 21/4 * t + 15/4 * t + 15/4 * 24 = 21 * 3 - (21/4 - 15/4) * t + 15 * 6 = 63 - 6/4 * t + 90 = 153 - 3/2 * t;
Подставим значение t = -0,4:
153 - 3/2 * (-0,4) = 153 + 3/2 * 4/10 = 153 + 3/5 = 153,6;
Ответ: 153,6.
Автор:
smudgeДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть